Spatial Location Optimization of Fire Stations with Traffic Status and Urban Functional Areas - Chen, Yuehong; Wu, Guohao; Chen, Yu; Xia, Zelong (Applied spatial analysis and policy, 2023)
Efficient spatial deployment of urban fire stations is highly desired to address the frequent and complex modern urban fires. Various spatial location optimization approaches have been developed to site fire stations. However, most approaches ignored the impact of the traffic status and the actual demand areas of fire services in the rapid urbanization. This paper develops a multi-objective spatial optimization model to account for the traffic status with the online map and the actual demands of fire services with urban functional areas in siting fire stations. A case study in Nanjing, China is conducted to select fire stations with the developed model. Results demonstrate its effectiveness in siting fire stations and highlighting important policy implications for fire departments to ensure urban safety and resilience.